Los homenajes a José Ingenieros y el debate en torno al papel del intelectual - Pita González, Alexandra (Revista Complutense de Historia de América, 2010)
This piece analyzes the posthumous tributes to Jose Ingenieros, with the objective of recovering the multiple social representations of this intellectual figure, as constructed by individuals or groups from the standpoints of Buenos Aires and Latin America. It is maintained that through these civic rituals one can observe the ways in which a varied and diverse number of images of Ingenieros were created in the collective memory. It is proposed that the existence of these diverse shades is due to the intention to symbolically appropriate the prestigious figure of Ingenieros –and to stand out as his worthy heirs- as well as to the difficulty of finding a single and coherent representation of the ideal intellectual.